Fashion From Home Sebagai Customer Relationship Management Toko Marks & Spencer Mall Kasablanka di Masa Pandemi Covid-19 - Sri Susinih Susanti; Dwi Kartikawati (Universitas Nasional, 2022)
This research focuses on how to implement Customer Relationship Management activities in the Fashion From Home program at the Marks & Spencer Kasablanka store, during the covid-19 pandemic. This research is qualitative. Method that used is a case study. The results showed that Customer Relationship Management activities are done through the Fashion From Home program were carried out to maintaining good relations with their customers and to improve services by utilizing internet technology. Customer Relationship Management (CRM) is a form of company effort to maintain communication with customers and utilize all forms of available information technology such as telephone, internet and mobile devices so that companies can understand customers more deeply than what is needed. The implementation of Customer Relationship Management activities at the Marks & Spencer Kota Kasablanka Store in the Fashion From Home program carried out during this pandemic is by implementing CRM elements, CRM applications, utilizing customer data bases, types of CRM, and the purpose of CRM. Penelitian ini berfokus pada bagaimana implementasi kegiatan Customer Relationship Management melalui program Fashion From Home di toko Marks & Spencer Kasablanka selama masa pandemi covid-19. Penelitian ini bersifat kualitatif. Metode yang digunakan adalah studi kasus. Hasil penelitian menunjukkan bahwa kegiatan Customer Relationship Management yang dilakukan melalui program Fashion From Home untuk menjaga hubungan baik dengan para pelanggannya dan meningkatkan pelayanan dengan memanfaatkan teknologi internet. Customer Relationship Management (CRM) merupakan bentuk upaya perusahaan untuk menjaga komunikasi dengan pelanggan dan memanfaatkan segala bentuk teknologi informasi yang tersedia seperti telepon, internet dan perangkat mobile sehingga perusahaan dapat memahami pelanggan lebih dalam dari yang dibutuhkan. Implementasi kegiatan Customer Relationship Management di Marks & Spencer Kota Kasablanka Store melalui program Fashion From Homeyang dilakukan selama masa pandemi ini adalah dengan mengimplementasikan elemen CRM, aplikasi CRM, pemanfaatan database pelanggan, jenis CRM, dan tujuan dari CRM.